Political Consciousness of Muhammadiyah: Historical Trajectories and Future - Ridho Al-Hamdi (Studia Islamika, 2022)
Muhammadiyah, as Indonesia’s largest Islamic reformist force, has survived for more than a century coping with political challenges. It is irresistible to further investigate its political identity through the inquiry of historical consciousness. This paper examines the formation, structure, and fate of the political consciousness of Muhammadiyah. Formation represents the past, structure indicates the present, and fate denotes the future. The findings demonstrate that the formation commenced from 1912 to 2020, splitting into two gradual phases: individual consciousness (1912-1971) and institutional consciousness (1971-2020). This trajectory has resulted in two structures of political reasoning in Muhammadiyah: scripturalist-rationalist as the dominant school and substantial-pragmatist as the marginalized one. Meanwhile, the politics of Muhammadiyah in the future will no longer involve instituting a political party. Instead, it is establishing centers of excellence to engineer political strategies and preserve actions operated by the “Muhammadiyah Caucus.”